Telitacicept for autoimmune nephropathy - Cai, Jingjing; Gao, Dan; Liu, Dongwei; Liu, Zhangsuo (Frontiers in Immunology, 2023)
B cells and their mediated humoral immunity play a key role in autoimmune diseases. The B-cell activating factor BAFF (also known as BLYS) and a proliferation-inducing ligand APRIL are essential for maintaining the B-cell pool and humoral immunity. BAFF and APRIL can bind to BR3/TACI/BCMA on B cells to promote B cell differentiation, maturation, and the secretion of antibodies by plasma cells. BAFF/APRIL overexpression is identified in various autoimmune diseases, such as rheumatoid arthritis, systemic lupus erythematosus, IgA nephropathy, etc. Telitacicept, a novel fully human TACI-Fc fusion protein that binds both BAFF and APRIL, was approved for treating systemic lupus erythematosus in March 2021 in China at a recommended dose of 160 mg/w subcutaneously and is in clinical trials for the treatment of multiple indications in other autoimmune disease areas. In this review, we explored Telitacicept's mechanism of action and clinical data. In addition, the immune features of autoimmune nephropathy were discussed, emphasizing lupus nephritis, IgA nephropathy, and membranous nephropathy.